Global Distribution and Seasonality of Martian Atmospheric HCl Explained Through Heterogeneous Chemistry - Paul M. Streeter; Kylash Rajendran; Stephen R. Lewis; Kevin S. Olsen; Alexander Trokhimovskiy; Oleg Korablev; Manish R. Patel (Geophysical Research Letters)
Abstract Recent observations from the ExoMars Trace Gas Orbiter (TGO) have revealed the presence of hydrogen chloride (HCl) in the martian atmosphere. HCl shows strong seasonality, primarily appearing during Mars' perihelion period before decreasing faster than projected from photolysis and gas‐phase chemistry. HCl profiles also display local anti‐correlation with water ice aerosol. One candidate explanation is heterogeneous chemistry. We present the first results from a heterogeneous chlorine chemistry scheme incorporated into a Mars global climate model (GCM), with atmospheric dust/water ice parameterized as an HCl source/sink respectively. Results were compared against a Mars GCM with gas‐phase only chlorine chemistry and observations from TGO's Atmospheric Chemistry Suite. We found that the heterogeneous scheme significantly improved the modeled HCl seasonal, latitudinal, and vertical distribution, supporting a crucial role for heterogeneous chemistry in Mars' chlorine cycle. Remaining discrepancies show that further work is needed to characterize the exact aerosol reactions involved.